PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS TERHADAP AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SEKOLAH MENENGAH ATAS NEGERI 2 TAMBANG - Ristiliana, Salmiah, Yulia Rizka PJH (Universitas Batanghari Jambi, 2019)
Abstract This study aims to determine the significant influence on the Talking Chip Type Cooperative Learning Model Against Student Learning Activities in the State 2 Mine High School, this research is motivated by students who still do not want to ask questions. There are still students who do not dare to express their opinions to the teacher or the theme, some students are less responsible for group learning. This research is a Quasi Experiment research. The form of design used in this study is Posttest-Only Design With Nonequivalent Group. The subjects in this study were students of class X IPS of State High School 2 Mine while the objects in this study were the Cooperative Learning Type Talking Chips Model for the learning activities of X IPS students in the State High School 2 Mine. Data is collected using observation. The documentation and data analysis techniques used are the normality test and homogeneity test using the SPSS program. the calculated value of tcount is 7.411 with the level of Sig. (2-tailed) is 0,000 with df = n-1 = 32-1 so that the value of ttable = 2.43 at a significant level α = 0.05 or 5% is received or the proposed hypothesis is accepted by obtaining the value tcount> ttable or 7.411 ˃ 2, 43. Keywords : Talking Chips, Learning Activities